HeLM: a macrophyte-based method for monitoring and assessment of Greek lakes - D. Zervas; I. Tsiripidis; V. Tsiaoussi (2018)
Zervas, D., Tsiaoussi, V. & Tsiripidis, I. HeLM: a macrophyte-based method for monitoring and assessment of Greek lakes. Environ Monit Assess 190, 326 (2018). https://doi.org/10.1007/s10661-018-6708-1